Pelatihan Dasar Ilmu Hisab Dan Implementasinya Kepada IPPNU Badas - Mustajib; As’ad Nizar (LP3M IAIFA Kediri, 2021)
The younger generation is the generation that becomes the hope of the nation's successor and religion. Successors in the social and scientific fields. In the field of science and worship, there are many problems experienced by young generic, one of which is related to attitudes towards religious organizations in Indonesia that vary including the steps of each organization. Based on this context, the basic training program of hisab science is carried out by researchers because they consider there is some kind of turmoil experienced by the IPPNU group in addressing the big differences between Nahdlatul Ulama and Muhammadiyah in making decisions related to mandatory worship. The training aims so that IPPNU member Badas can understand the causes of the differences in steps taken by Nahdlatul Ulama and Muhammadiyah along with the foundations used in taking their respective big steps. This training is fairly successful if you look at the response and steps taken by the trainees after this training program is implemented.